광음향 분광법을 이용한 부생가스 발전시설의 N₂O 배출계수 연구 - 김수빈(Kim, Subin); 조승현(Jo, Seunghyun); 강성민(Kang, Sungmin); 전의찬(Jeon, Eui-chan) (한국기후변화학회지, 2024)
By-products of steel production facilities include Coke Oven Gas, Blast Furnace Gas, and Linz-Donawitz converter Gas. And the CO2 emission factor and calorific value were developed and announced in 2022 through related research in Korea, but study or research about Non-CO2 emission is insufficient. The IPCC guidelines recommend developing a national emission factor (Tier 2) or emission factor per unit facility (Tier 3) when calculating greenhouse gas emissions. Research related to Non-CO2 emitted from by-product gas is needed to increase the reliability of the greenhouse gas inventory. This study confirmed the emission characteristics of N2O for the power plant using by-product gas and developed the N2O emission factor of power plants using by-product gas. The PAS method, one of the real-time measurement method, was used to measure the N2O concentration of by-product gas power plant. The facility to be studied was selected for one of the two domestic facilities that generate power using by-product gas. The final exhaust gas is emitted through the by-product gas after combustion, and the N2O concentration was measured for a total of 6 days in this study. The average N2O concentration of by-product gas power plant in this study was 0.34 ppm. The N2O emission factor of this study was 0.69kgN2O/TJ, with a maximum value of 0.98kgN2O/TJ and a minimum value of 0.57kgN2O/TJ. This study developed the N2O emission factor of domestic by-product gas power plants for the first time, and it is believed that it can contribute to increasing the reliability of the national greenhouse gas inventory. KCI Citation Count: 0